POTRET KORUPTOR DALAM NOVEL KORUPSI - Ni Nyoman Subardini (Pujangga: Jurnal Bahasa dan Sastra, 2015)
ABSTRACT This paper aims to describe about of fenomena corruption in two novels. The method of research used is qualitative description method. The novels being discussed are Korupsi written by Pramoedya Ananta Toer (2002), and Korupsi (translation) written by Tahar Ben Jelloun (2010). Under the descriptive study by using continually reading technique, it was identified that there are information about corruption. One’s acts are closely related to the place or the invironment where she/he lives. This statement is relevant with concept of “Sosiologi is objektif study and scientific approach about society and man, study about social process and institution” by Sapardi Djoko Damono (1979). By using the sociological approach of literature, the study shows that corruption committed by the main character of Korupsi caused by poverty and the opportunity possessed by a public servant. With this assumption, we can make the novel as a document in expressive research.Based on the analysis report, it is found out that corruption in a phenomenon that has been cultured in the society. Corruption is a phenomenon is as old as human life. Corruption phenomenon has taken place in various forms and society or countries. In its history, corruption by society is condidered as a natural thing in everyday life. Key words: novel, corruption, sosiology literature ABSTRAK Penelitian ini bertujuan mendeskripsikan fenomena korupsi dalam dua novel. Metode penelitian yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Novel yang dibicarakan adalah Korupsi karya Pramoedya Ananta Toer (2002), dan Korupsi (terjemahan) karya Tahar Ben Jelloun (2010). Mendeskripsikan dengan teknik membaca berulang-ulang, akan dapat mengidentifikasikan keterangan tentang korupsi. Pendekatan yang dipergunakan adalah sosiologi sastra, suatu analisis teks untuk mengetahui strukturnya, untuk kemudian dipergunakan memahami lebih dalam lagi gejala sosial yang ada di luar sastra (Damono, 1979).Berdasarkan hasil analisis diperoleh korupsi sebagai fenomena yang telah membiadab di masyarakat. Korupsi sebagai suatu gejala sosial telah berada setua dengan umur umat manusia. Fenomena korupsi telah mengambil tempat pada berbagai bentuk dan terdapat pada berbagai masyarakat atau bangsa. Dalam sejarahnya, korupsi oleh masyarakat dianggap sebagai sesuatu yang wajar atau lazim dalam kehidupan sehari-hari. Kata kunci: novel, korupsi, sosioliogi sastra